Synthesis and characterization of poly(ester-urethanes) base on hydroxylauric acids and L-Lactic acid - Casalme, Loida O.; Sumera, Florentino C. (Quezon City Institute of Chemistry, College of Science, University of the Philippines Diliman, 2013)
In a two-step polymerization reaction which involved prepolymer synthesis followed by chain elongation, a poly(ester-urethane) polymer was synthesized to meet the essential requirements of a biodegradable biomaterial. First, lauric acid was oxidized to hydroxylauric acid using the triflouroacetic acid-hydrogen peroxide reagent resulting to a mixture of monohydroxylauric acids with lactones as by products. The monohydroxylauric acid mixture and lactones were successfully characterized by GCFID and GC-MS.
Thesis (M.S.- Chemistry) --University of the Philippines Diliman
Keywords: Polymerization